Comparison of the Whole Cell Proteome and Secretome of Epidemic Bordetella pertussis Strains From the 2008–2012 Australian Epidemic Under Sulfate-Modulating Conditions - Luu, Laurence Don Wai; Octavia, Sophie; Zhong, Ling; Raftery, Mark J.; Sintchenko, Vitali; Lan, Ruiting (Frontiers in Microbiology, 2018)
Sulfate is an important modulator for virulence factor expression in Bordetella pertussis, the causative organism for whooping cough. During infection, sulfate is released when respiratory epithelial cells are damaged which can affect gene expression. The current predominant strains in Australia are found in SNP cluster I (ptxP3/prn2). It has been reported that ptxP3 strains have higher mRNA expression of virulence genes than ptxP1 strains under intermediate sulfate modulating conditions (5 mM MgSO4). Our previous proteomic study compared L1423 (cluster I, ptxP3) and L1191 (cluster II, ptxP1) in Thalen-IJessel (THIJS) media without sulfate modulation and identified an upregulation of transport proteins and downregulation of immunogenic proteins. To determine whether proteomic differences exist between cluster I and cluster II strains in intermediate modulating conditions, this study compared the whole cell proteome and secretome between L1423 and L1191 grown in THIJS media with 5 mM MgSO4 using iTRAQ and high-resolution multiple reaction monitoring. Two proteins (BP0200 and BP1175) in the whole cell were upregulated in L1423 (fold change (FC) > 1.2, false discovery rate (FDR) < 0.05). In the secretome, four proteins from the T3SS effectors were downregulated (FC < 0.8, FDR < 0.05) while six proteins, including two adhesins; pertactin (Prn) and tracheal colonisation factor A (TcfA), were upregulated which were consistent with our previous proteomic study. The upregulation of Prn and TcfA in SNP cluster I may result in improved adhesion while the downregulation of the T3SS and other immunogenic proteins may reduce immune recognition, which may contribute to the increased fitness of cluster I B. pertussis strains.